2009
DOI: 10.1007/s10762-009-9529-z
|View full text |Cite
|
Sign up to set email alerts
|

The Numerical Simulation Study of Pseudospark Hollow Cathode Discharge

Abstract: Pseudospark discharges are sources of intense electron beams. Reported in this paper are theoretical studies of the Pseudospark discharges. A theoretical and computational model has been adopted to study the initiation phase of Pseudospark discharges via a twodimensional electrostatic particle-in-cell plus Monte Carlo (PIC-MCC) collision method. From the numerical results, a sequence of physical events has been identified. It has been found that the ionization processes determined by local electric field and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Apparently, the potential change in the virtual anode region is relatively small. According to the simulation results, it can be found that the discharge process in the simulation is in accordance with the conclusions of other researchers, [17,19,22] which proves the effectiveness of the simulation.…”
Section: Results and Analysessupporting
confidence: 83%
See 1 more Smart Citation
“…Apparently, the potential change in the virtual anode region is relatively small. According to the simulation results, it can be found that the discharge process in the simulation is in accordance with the conclusions of other researchers, [17,19,22] which proves the effectiveness of the simulation.…”
Section: Results and Analysessupporting
confidence: 83%
“…[13][14][15][16] Numerical simulation was also a feasible method with the help of particle in cell (PIC) and Monte Carlo collision (MCC) methods. [17][18][19][20][21][22] Some researchers studied the discharge mechanism by simulating the PS discharge, [17][18][19][20] and others investigated the influences of various operating conditions on the discharge current. [20][21][22] However, the electron beam produced by the PS-sourced may have a relatively large velocity spread due to the collisions of electrons with other particles.…”
Section: Introductionmentioning
confidence: 99%
“…They do not need a magnetic field, which makes them particularly useful for sputtering of ferromagnetics. Hollow cathodes are used as intensive light sources [1], spectroscopic light sources [2], cluster sources [3], electron beam sources [4,5], ion thrusters [6] and for deposition [7][8][9][10]. The most important part of an HC is its hollow cathode cylinder.…”
Section: Introductionmentioning
confidence: 99%